Is the measurement of blood pressure by automatic monitor in the South American pediatric population accurate? SAYCARE Study (2018)
ABSTRACT: This study aimed to test the validity of an automatic oscillometric device to measure the blood pressure (BP) in children (n 5 191) and adolescents (n 5 127) aged 3 to 18 years.Methods: Systolic BP (SBP) and diastolic BP (DBP) levels were measured simultaneous by automaticdevice and mercury column with Y-connection. To verify the validity, Bland-Altman plots and limits of agreement of 95% (95% LOA), specificity and sensitivity of the device, and the grade of British Hypertension Society (BHS) criteria were used. Results: The monitor measurements demonstrated lower measurement bias (mean difference [95% LOA]): 1.4 (29.9 to 12.8) mmHg in children and 4.3 (27.8 to 16.5) mmHg in adolescents for SBP. For DBP, it was 2.2 (27.4 to 11.7) mmHg in children and 1.4 (28.4 to 11.1) mmHg in adolescents. The sensitivity in children was 21.4 (95% CI 5 16.3-26.6), and in adolescents, it was 20.0 (95% CI 5 13.2-26.8); the specificity was 95.9 (95% CI 5 93.4-98.4) in children and 100.0 (95% CI 5 100.0-100.0) in adolescents. The monitor-tested ratings are Grade B for SBP in children and SBP and DBP in adolescents and Grade C for DBP in children. Conclusions: The automatic monitor presented high values of specificity and lower values of sensitivity to the diagnosis of HBP; however, it can be considered accurate (lower measurement bias) and valid for epidemiological and clinical practice in accordance with BHS criteria.